Neurotensin and its high affinity receptor 1 as a potential pharmacological target in cancer therapy - Wu, zherui; Martinez-Fong, Daniel; Trédaniel, Jean; Forgez, Patricia (Frontiers in Endocrinology, 2013)
Cancer is a worldwide health problem. Personalized treatment represents a future advancement for cancer treatment, in part due to the development of targeted therapeutic drugs. These molecules are expected to be more effective than current treatments and less harmful to normal cells. The discovery and validation of new targets are the foundation and the source of these new therapies. The neurotensinergic system has been shown to enhance cancer progression in various cancers such as pancreatic, prostate, lung, breast and colon cancer. It also triggers multiple oncogenic signaling pathways, such as the PKC/ERK and AKT pathways. In this review, we discuss the contribution of the neurotensinergic system to cancer progression, as well as the regulation and mechanisms of the system in order to highlight its potential as a therapeutic target, and its prospect for its use as a treatment in certain cancers.